Discovering Disciplinary Linguistic Knowledge with English Learners and Their Teachers: Applying Systemic Functional Linguistics Concepts through Design-Based Research - Moore, Jason; Schleppegrell, Mary; Palincsar, Annemarie Sullivan (TESOL quarterly, 2018)
A focus on how language varies in its forms and meanings can help English learners (ELs) in K-12 classrooms engage in disciplinary discourses that enable them to learn both language and content. Systemic functional linguistics (SFL) offers promising ways of talking about language in support of disciplinary learning. SFL's meaning-based metalanguage offers analytical tools for making sense of text, but its description of complex systems in language is not readily accessible to teachers and students. This article offers a case study of how a design-based research (DBR) process yielded findings, materials, and instructional theory over a 3-year project to develop SFL-based approaches to engaging ELs in talk about language. In this study, conducted in an urban school district in the midwestern United States, the authors worked collaboratively with teachers and literacy coaches at six schools with high proportions of ELs, supporting them in using SFL metalanguage to talk about language and meaning as they engaged in grade-appropriate literacy activities: reading and responding to texts and writing subject-specific arguments. This article shares both what the authors learned about the implementation of SFL pedagogies and the affordances of DBR methodology for learning to apply a complex theory to support ELs.